Biological approach to synthesize TiO2 nanoparticles using Aeromonas hydrophila and its antibacterial activity - Jayaseelan, Chidambaram; Rahuman, Abdul Abdul; Roopan, Selvaraj Mohana; Kirthi, Arivarasan Vishnu; Venkatesan, Jayachandran; Kim, Se-Kwon; Iyappan, Moorthy; Siva, Chinnadurai (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2013)
Development of reliable and eco-friendly process for synthesis of metal oxide nanoparticles is an important step in the field of application of nanotechnology. Titanium dioxide (TiO2 NPs) nanoparticles were synthesized using the bacteria Aeromonas hydrophila. The synthesized particles were subjected to characterization by FTIR, XRD, FESEM and AFM. Non-contact mode AFM images of the TiO2 NPs find the topological appearance and the size. The range was found to be 28–54 and the individual particle size was 40.50nm. [Display omitted] . ► Aeromonas hydrophila mediated biosynthesis of TiO2 NPs was achieved. ► Glycyl-l-proline plays an important role as a capping and stabilizing agent. ► XRD confirmed the crystalline nanoparticles of 40.50nm in size. ► FESEM analysis showed smooth in shape, spherical and uneven. ► TiO2 NPs exposed great inhibition zone in S. aureus (33mm) and S. pyogenes (31mm). Nanosized materials have been an important subject in basic and applied sciences. A novel, low-cost, green and reproducible bacteria, Aeromonas hydrophila mediated biosynthesis of titanium dioxide nanoparticles (TiO2 NPs) was reported. The resulting nanoparticles were characterized by FTIR, XRD, AFM and FESEM with EDX. FTIR showed characteristic bands (1643 and 3430cm−1) finds the role of carboxyl group OH stretching amine NH stretch in the formation of TiO2 NPs. The XRD spectrum confirmed that the synthesized TiO2 NPs were in the form of nanocrystals, as evidenced by the peaks at 2θ values of 27.47°, 31.77°, 36.11°, 41.25°, 54.39°, 56.64° and 69.54° were identified as 110, 100, 101, 111, 211, 220 and 301 reflections, respectively. The crystallite sizes were calculated using Scherrer’s formula applied to the major intense peaks and found to be the size of 40.50nm. The morphological characterization was analyzed by FESEM and the analysis showed the NPs smooth shaped, spherical and uneven. GC–MS analysis showed the main compounds found in A. hydrophila were uric acid (2.95%), glycyl-l-glutamic acid (6.90%), glycyl-l-proline (74.41%) and l-Leucyl-d-leucine (15.74%). The potential glycyl-l-proline could have played an important role as a capping agent. A possible mechanism for the biosynthesis of TiO2 NPs has been proposed. The antibacterial activity of the synthesized TiO2 NPs was assessed by well diffusion method toward A. hydrophila, Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Streptococcus pyogenes and Enterococcus faecalis and showed effective inhibitory activity against S. aureus (33mm) and S. pyogenes (31mm).